Republic of Croatia : 2019 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report, 2020)
This 2019 Article IV Consultation with the Republic of Croatia discusses that it experienced its fifth consecutive year of solid economic growth, once again driven largely by private consumption and tourism. Employment gains have been robust, wages have continued to rise, while import prices have helped to keep inflation muted. Increased absorption of European Union funds is likely to raise public investment in the coming years. In conjunction with continued strong consumption, the current account surplus is expected to decline, and turn into a moderate deficit, while economic growth moderates. Both public and external indebtedness are expected to continue their declining trajectories. The pace of fiscal consolidation in 2019 continued to slow, with the budget estimated to be close to balance. Contingent liabilities could also pressure budget balances in the coming years.